Water management in a tank cascade irrigation system in Sri Lanka: first seasonal report of TARC-IIMI Joint Project 1991/1992 Maha Season - Itakura, J.; Abernethy, Charles L. (International Irrigation Management Institute, 1993)
IRRIGATION Management Institute (IIMI) and the Tropical Agriculture Research Center (TARC), Ministry of Agriculture, Forestry and Fisheries of Japan, initiated a collaborative study in August 1991. This joint study is focused on small-scale tank irrigation systems which are spread over the Dry Zone of Sri Lanka, and is conducted with the assistance of Sri Lanka's Department of Agrarian Services.